Sensory integration and its importance in learning for children with autism spectrum disorder. - Vives-Vilarroig, Juan; Ruiz-Bernardo, Paola; García-Gómez, Andrés (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2022)
Sensory integration is supported by multiple theoretical backgrounds that justify its importance in order to integrate the information coming from the different senses and to develop an adapted response to the environment. Scientific literature has also shown that there is a close relationship between sensory integration and learning. The aim of this article is to address the concept of sensory integration and its influence on learning, especially in children with Autism Spectrum Disorder (ASD). The methodology used was a narrative literature review, guided by the aim of the research. The databases consulted were: Web of Science, SCOPUS, Dialnet and RedaLyC. The main descriptors used were Sensory Integration, Learning and ASD. The results obtained support the idea that children with ASD often present difficulties in this sensory integration process, and that this is the explanatory cause of some of the learning and behavioural problems they present. It is hoped that this work will raise awareness of the need to consider this aspect during diagnosis and/or intervention in order to favour the genuine inclusion of children with ASD in society.